Overdamped modes in Schwarzschild-de Sitter and a Mathematica package for the numerical computation of quasinormal modes - Jansen, Aron (European physical journal plus, 2017)
. We present a package for Mathematica that facilitates the numerical computation of the quasinormal mode (QNM) spectrum of a black hole/black brane. Requiring as input only the QNM equation(s), the application of a single Mathematica function will compute the spectrum efficiently, by discretizing the equation(s) and solving the resulting generalized eigenvalue equation. It is applicable to a large variety of black holes, independently of their asymptotics. The package comes fully documented and with several tutorials. Here we present a self-contained review of the method and consider several applications. We illustrate the method in the simplest case of scalar QNMs of a Schwarzschild black brane in anti-de Sitter. Then we go on to look at the scalar QNMs of the Schwarzschild black hole in de Sitter, in anti-de Sitter and in asymptotically flat spacetimes, finding a novel infinite set of purely imaginary modes in the first case. We also derive the QNM equations for a generic Einstein-Maxwell-scalar background and use these to compute the QNMs of the asymptotically anti-de Sitter Reissner-Nordström black brane, as a further illustration and check of the method.